Comprehensive genomic analysis of five kindreds with multiple childhood leukemias: importance of individual functional analysis for rare ETV6 germline variants - Ai Yamada; Shun Nagasawa; Midori Nakagawa; Sachiyo Kamimura; Nami Inoue; Hiroyoshi Watanabe; Masatoshi Takagi; Yuhki Koga; Dai Keino; Hideki Nakayama; Jun Yoshimura; Koichiro Doi; et al. (Human Cell, 2026)
Germline variants in leukemia predisposition genes are increasingly detected in pediatric patients. Nevertheless, the rare variants identified in diagnostic samples may be misinterpreted without variant-level functional evaluation and cautious clinical interpretation. Whole-exome sequencing was performed on 28 individuals from five kindreds in which at least two children developed acute leukemia. Results identified a rare ETV6 variant, c.604C > G (p.Arg202Gly), in monozygotic twins with ETV6::RUNX1 -positive B-cell precursor acute lymphoblastic leukemia. To support variant interpretation, HeLa-cell populations stably expressing FLAG-tagged wild-type ETV6 and p.Arg202Gly and the known loss-of-function control p.Pro214Leu were established. Subcellular localization was assessed via immunofluorescence microscopy with quantitative scoring. Transcriptional repression was evaluated using luciferase reporter assays driven by ETV6 target promoters ( MMP 3 and PF4 ). p.Arg202Gly predominantly showed nuclear localization comparable to WT, whereas p.Pro214Leu was enriched in the cytoplasm. In the reporter assays, similar to WT, p.Arg202Gly retained repression activity. Meanwhile, p.Pro214Leu failed to repress both reporters. The in-silico prediction of nuclear export sequences suggested an additional export signal in p.Pro214Leu, but not in p.Arg202Gly. Collectively, these findings indicate that p.Arg202Gly behaves as WT-like in the assays performed and do not support a loss-of-function effect. Our study emphasizes the importance of variant-level functional assessment for rare ETV6 variants to inform clinical interpretation and avoid overestimation of pathogenicity.

Rapid and easy determination of mycotoxin nivalenol in wheat and barley by direct competitive enzyme-linked immunosorbent assay - Ritsuto Sekizuka; Keiko Kitsunezuka; Norichika Miyano; Hiroyoshi Inoue; Atsushi Miyasaka; Hiroyuki Nakagawa; Kenji Oonaka; Masayo Kushiro; Shiro Miyake (Food Control, 2025)

Fish assemblage structure response to seagrass bed degradation due to overgrazing by the green sea turtle Chelonia mydas at Iriomote Island, southern Japan - Hiroyuki Inoue; Akira Mizutani; Kusuto Nanjo; Kouki Tsutsumi; Hiroyoshi Kohno (Ichthyological Research, 2021)

Gibberella ear rot of corn caused by Fusarium asiaticum in Japan - Akira Kawakami; Naoki Kato; Takahide Sasaya; Keisuke Tomioka; Hiroyoshi Inoue; Atsushi Miyasaka; Kazuyuki Hirayae (Journal of General Plant Pathology, 2015)

Distribution and multiplication of Ralstonia solanacearum in tomato plants with resistance derived from different origins - Kazuhiro Nakaho; Hiroyoshi Inoue; Tomohiko Takayama; Hisayoshi Miyagawa (Journal of General Plant Pathology, 2004)